The Spread of Droplets and Aerosols of Surgical Motor Handpiece Irrigation Using Different Suction Systems - James K. H. Tsoi; Hao Ding; Ki Hon; Yiu Yan Leung (Frontiers Media S.A., 2021)
Objective: This study aimed to compare the effectiveness of various combinations of dental suction devices in reducing the amount and distance of spread of aerosols and droplets using an electrical surgical motor model with a self-irrigation system.Materials and Methods: In a standard single-chaired air-conditioned ventilated dental clinic, an electrical dental surgical motor with a high-speed handpiece (Implantmed) cooled with 0.2% fluorescein containing normal saline was used to drill a gypsum block mounted on a phantom head in a supine position. A single operator performed thrice each of the following suction settings: (a) no suction, (b) low-volume suction, (c) low-volume + high-volume suctions, and (d) low-volume + external oral suctions. Aerosols (0.1-5 μm) were measured with a particle counter at the mouth opening of the phantom head, and droplet sizes and distances were analyzed via a machine learning algorithm by identifying fluorescence droplets on pre-loaded pieces of paper on the floor for each group.Results: The different suction systems have different performances in terms of droplet distance (p = 0.007), whereas using (c) high volume suctions (41.1 ± 22.9 cm) and (d) external oral suction unit (39 ± 18.2 cm) had significantly reduced the spread of droplets when compared with (a) without suction (58.9 ± 17.1 cm). Using (d) external oral suction or (c) high volume suction could reduce the number for all droplet sizes. The use of (c) high volume suction was most effective in reducing aerosol count of 0.3-1 μm, while (d) external oral suction was most effective in reducing aerosol count of 3-5 μm.Conclusions: Both external oral suction and high-volume suction were effective in reducing aerosols and droplets generated by the irrigation of a surgical high-speed motor handpiece. External oral suction could be an effective alternative to high volume suction in dental surgical procedures to reduce the spread of aerosols and droplets.Clinical Relevance: External oral suction or high-volume suction should be used in conjunction with low-volume suction in surgical procedure to reduce the spread of aerosols and droplets in a dental clinic environment.